Politicians and the War, 1914-1916 - Beaverbrook, The Rt. Hon. Lord (London Thornton Butterworth Limited, 1928)
"I have decided to call it "Politicians & the War," for the object of the book is to deal with political events at home in contradistinction to military events abroad. It is designed to emphasize the immense importance of what may be called the civilian aspect of war direction--a thing which war-books tend to neglect."
Include Illustrations, Appendix and Index.
Keywords: Great Britain -- World War (1914-1918) -- Politics and government -- Statesmen -- Politicians -- Political science